Developing classroom management skills for pre-service primary education students through pedagogical training in Vietnam - Hai, Ta Van (International research journal of management, IT and social sciences, 2023)
The article focuses on the development of classroom management skills for pre-service primary education students through pedagogical training. The study employs a literature review method to explore various pedagogical training approaches designed to enhance classroom management abilities for future teachers. The article highlights the significance of a strong theoretical foundation in classroom management. Pre-service teachers need to grasp essential concepts and theories related to classroom management to effectively address challenges in the classroom and foster a positive learning environment. Moreover, practical strategies, such as behavior management techniques and setting clear expectations, are emphasized as crucial elements for developing classroom management skills. Additionally, the article emphasizes the positive impact of teacher-student relationships on effective classroom management. Building rapport with students, showing empathy, and creating a supportive learning environment are identified as critical factors in successful classroom management. Furthermore, the article stresses the importance of personalized support in classroom management. Pre-service teachers should be equipped with strategies to address the diverse behaviors and learning needs of their students, ensuring that each student receives appropriate guidance and assistance. The practical implications of the research findings lie in the design and enhancement of comprehensive and practical pedagogical training programs for pre-service primary education students.